Analysis of the Effect of Store Atmosphere, Price Discount, and Sale Person on Impulse Buying, with Shopping Lifestyle and Emotional Response as Mediation Variables Study on UNIQLO Products Consumers in Yogyakarta - Kristina DetaNatasya; Herry Maridjo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine: (1) the effect of store atmosphere on impulse buying with emotional response as a mediating variable, (2) the influence of store atmosphere on impulse buying with shopping lifestyle as a mediating variable, (3) the effect of price discount on impulse buying by emotional response as a mediating variable, (4) the effect of price discounts on impulse buying with shopping lifestyle as a mediating variable, (5) the influence of sales persons on impulse buying with emotional responses as mediating variables, (6) the influence of sales persons on impulse buying with shopping lifestyle as a mediating variable. The population in this study were all consumers of Uniqlo products. Sampling using the purposive sampling method, namely consumers who have purchased Uniqlo brand fashion products at the Uniqlo store at least 2 times within 3 months with a total of 100 respondents. Data collection techniques using a questionnaire. Data analysis using Structural Equation Modeling (SEM) with WarpPLS approach, Warp PLS software version 6.0.m3. The results of the study prove that. (1) Store atmosphere has a positive and significant influence on impulse buying with emotional response as a mediating variable. (2) Store atmosphere has a positive and significant influence on impulse buying with shopping lifestyle as a mediating variable. (3) Price discount has a positive and significant effect on mpulse buying with emotional response as a mediating variable. (4) Price discount has significant effect on impulse buying with shopping lifestyle as a mediating variable. (5) Sales person has a positive and significant influence on impulse buying with emotional response as a imediating. (6) Sales person has no positive and significant effect on impulse buying with shopping lifestyle as a mediating variable